Efeitos da incorporação do chamote no processamento e microestrutura da cerâmica utilitária do município de Bragança-PA - SANTOS, Dayana Rosy Souza dos (2019)
The objective of this work is to evaluate the effect of the incorporation of in a mass of utilitarian ceramics, aiming at obtaining refractory pans in the city of Bragança-PA. The shrimp was obtained from tailings of artifacts and handcrafted pots, burned at a temperature of 1000 ° C. Initially, the clay used in the manufacture of ceramics was subjected to chemical, physical and mineralogical characterization tests. The clay, silt and sand fractions, moisture and organic matter contents and mineralogical composition were quantified, the latter being by diffraction -X, thermal analysis (TG/ATG). Chamotte additions were made in the proportions of 5, 10, 15, 20, 25% by weight and subsequent preparation of the test specimen by hand, for burning in an industrial oven at a temperature similar to that used in the manufacture of the handmade ceramics in study. The evaluated properties were: water absorption, apparent porosity, fire loss, and linear retraction. Micrographs obtained by scanning electron microscopy with spectrometer of energy dispersion (SEM/EDS) and X-Ray (FRX). The results obtained were evaluated the behavior of the chamote in the incorporation referring to the drying parameters of the ceramic. In addition, the addition of chamote resulted in significant changes in porosity after burning. With the results of the study the definition of the 15% blend was reached, being the most indicated to avoid degenerative changes in the microstructure of the utilitarian ceramics produced in the São Mateus Community, also reducing the waste of raw material.